Impact and Possible Mechanism(s) of Adipose Tissue-Derived Mesenchymal Stem Cells on T-Cell Proliferation in Patients With Rheumatic Disease - Kuca-Warnawin, Ewa; Olesińska, Marzena; Szczȩsny, Piotr; Kontny, Ewa (Frontiers in Physiology, 2022)
Objectives: Systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) are chronic wasting, incurable rheumatic diseases of autoimmune background, in which T cells play a critical pathogenic role. Autologous adipose tissue-derived mesenchymal stem cells (ASCs) may represent an alternative therapeutic option for SLE and SSc patients, but the biology of these cells is poorly understood. Methods: Herein, we evaluated the anti-proliferative impact of ASCs of healthy donors (HD/ASCs, 5 reference cell lines), SLE patients (n = 20), and SSc patients (n = 20) on T lymphocytes. To assess the direct and indirect pathway of ASCs action, peripheral blood mononuclear cells (PBMCs) and purified CD4+ T cells of HD were activated and co-cultured in cell-to-cell contact (C-C) and transwell (T-W) conditions with untreated or cytokine (TNF + IFNΥ, TI)-licensed ASCs, then analyzed by flow cytometry to rate the proliferation response of CD8+ and/or CD4+ T cells. The concentrations of kynurenines, prostaglandin E2 (PGE2), interleukin 10 (IL-10), and transforming growth factor β (TGFβ) were measured from culture supernatants. Specific inhibitors of these factors (1-MT, indomethacin, and cytokine-neutralizing antibody) were used to assess their contribution to anti-proliferative ASCs action. Results: All tested ASCs significantly decreased the number of proliferating CD4+ and CD8+ T cells, the number of division/proliferating cell (PI), and fold expansion (RI), and similarly upregulated kynurenines and PGE2, but not cytokine levels, in the co-cultures with both types of target cells. However, TI-treated SLE/ASCs and SSc/ASCs exerted a slightly weaker inhibitory effect on CD4+ T-cell replication than their respective HD/ASCs. All ASCs acted mainly via soluble factors. Their anti-proliferative effect was stronger, and kynurenine levels were higher in the T-W condition than the C-C condition. Blocking experiments indicated an involvement of kynurenine pathway in inhibiting the number of proliferating cells, PI, and RI values as well as PGE2 role in decreasing the number of proliferating cells. TGFβ did not contribute to ASCs anti-proliferative capabilities, while IL-10 seems to be involved in such activity of only SLE/ASCs. Conclusion: The results indicate that SLE/ASCs and SSc/ASCs retain their capability to restrain the expansion of allogeneic CD4+ and CD8+ T cells and act by similar mechanisms as ASCs of healthy donors and thus may have therapeutic value.